Bilateral Carotid Body Paragangliomas - Literature Review and Comments in a Patient with no Signs of Men Syndrome - Sarafoleanu, C (Acta endocrinologica (Bucharest, Romania : 2005), 2023)
Paragangliomas are rare neuroendocrine slow-growing tumors, often asymptomatic, that originate from embryonic neural crest cell. In the head and neck area, the most common location is the carotid body, followed, with decreasing frequency, in jugular, tympanic and vagal sites. Bilateral carotid body tumors are extremely rare. To present the most important features of carotid body paragangliomas, illustrating the clinical characteristics, associated with a thorough analysis of the diagnostic imaging elements, but also the current therapeutic strategies, with respective anatomical, surgical considerations and potential complications that can occur. Surgical resection is the main line of treatment. The complex anatomy of the cervical region and the close relationships of carotid body paragangliomas with carotid vessels and cranial nerves, as well as its intense vascularization makes the surgical intervention a real challenge even for an experienced surgeon. Starts from a bilateral carotid paraganglioma in a 35-year-old male, with painless lateral neck swelling, accidentally discovered by his barber about two years ago. Diagnosis was suspected on the basis of history, clinical and radiological findings. "Wait and scan" strategy plus endocrinologic assessment for MEN syndromes were considered the optimal therapeutic approach in this case.